Study on Heart Measurements of the People between the Age 20-40 Years Present to the Teaching Hospital Colombo North – Post Mortem Study - De Lasantha. S. K. De Silva; Priyanath DC; M.M.A.C Gunathilake (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Presence of an enlarged heart provides a basis for determination of the cause and mechanisms of death. Gender, physical activity, and Body Mass Index (BMI) may affect the sizeof organs. Knowledge on such normal variations is needed in order to recognize theabnormalities.Objectives- This research was conducted to study the dimensions of the heart(heart weight, left ventricular thickness and valvular circumferences) among the young adult healthy deceased autopsies and evaluate their association with differentvariables.Methods: It was a descriptive cross-sectional study and 20-40 years of age healthy, young, adult, males and females in equal numbers who had died suddenly were studied by considering the inclusion and exclusion criteria. Details of the past history and the measurements were enteredinto a proforma and the anonymous data wereused for analysis.Results: The study revealed that the mean values of the heartweight was 280.52g (SD+/- 42.60), it was 293.94g (SD+/-39.29) for males and 267.10g (SD+/-42.64) for females. There was no significant association of heart weight with gender (P= 0.46410). There was a significant association between BMI and the heart weight of the females (P= 0.0387), no such association for left ventricular wall thickness. Further, there was a significant difference of the tricuspid valve circumference among two genders and the values were 11.6cm (SD+/-0.82) for males and 10.7cm (SD+/-0.6) forfemales.Conclusions: Majority of the findings was consistent with the findings of the studies globally on Caucasians. Increased body mass index was significantly associated with increased heart weight among females which could probably be explained as a consequence of increased epicardial fat since there was no such association for left ventricular wallthickness.